Quantifying influence of tillage practices on soil aggregate microstructure using synchrotron‐based micro‐computed tomography. (5th September 2021) - Gao, Yan; Liang, Aizhen; Fan, Ruqin; Guo, Yafei; Zhang, Yan; McLaughlin, Neil; Chen, Xuewen; Zheng, Haifeng; Wu, Donghui
Abstract: Studying the internal structure of soil aggregates is an insightful way to improve the understanding of soil aggregation process. However, it is still not clear how the macroaggregate pore structure is influenced by the application of long‐term tillage practices. In this study, we aimed to determine the differences in macroaggregate pore structure among long‐term tillage practices using micro‐computed tomography (SR‐μCT). Soil samples were collected from no tillage (NT) and ridge tillage (RT) plots and surrounding fields under conventional tillage (CT) and uncultivated soils (CK). The results showed that the diameters of most pores were greater than 30 μm, but >100 μm pores had the greatest percentage of total macroaggregate porosities in all four soils, that is NT, RT, CT and CK. The CK soil had a higher aggregate porosity of <30 μm and 30–60 μm, as well as a lower porosity of >100 μm than the NT, RT and CT soils. Total porosities within soil macroaggregates in both CK and CT were significantly lower than those in RT and NT, but the porosities of 30–60 μm and 60–100 μm within soil macroaggregates in both CK and RT were no significance. There were no significant differences in pore parameters between CK and RT. The CK and RT had higher mean weight diameter (MWD) and aggregate‐associated SOC contents than CT. Therefore, the pore structure of RT was similar to CK with good soil structure. Overall, RT was more appropriate tillage system to protect soil aggregate structure in black soils of Northeast China.